Export diversification through public investment in cultural tourism: Insights from a multi-regional model of Bolivia - Onil Banerjee; Martín Cicowiez; Adela Moreda (Inter-American Development Bank (IDB), 2019)
The growth of cultural tourism globally has presented an important opportunity for public investment in tourism to drive economic development in developing countries. With Bolivia's regional disparities in income and opportunity, it is critical to understand the regionally differentiated welfare impacts of public investment. We develop a first multi-regional economy-wide model for Bolivia and apply it to the economic analysis of a US26 million investment in tourism to diversify export earnings and reduce poverty. While the framework is more data intense than national level economy-wide models, a multi-regional approach is powerful for shedding light on regional trade-offs, benefits and costs, and enables analysis of smaller investment and demand shocks than that typically possible in a national level framework
Keywords: D58; Q56; Z3; 330; ex-ante economic impact evaluation; cost-benefit analysis; public investment in tourism development